Pengaruh Pengetahuan Peraturan Perpajakan, Kesadaran Wajib Pajak, Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Berkat Veryfi Putra Laia (CV. ITTC INDONESIA, 2025)
This study aims to analyze whether there is an influence between knowledge of tax regulations, taxpayer awareness, tax sanctions on individual taxpayer compliance at the Serpong Pratama Tax Service Office. The approach used in this study is a quantitative approach. The population in this study were taxpayers registered at the Serpong Pratama Tax Service Office. The data used is primary data obtained through questionnaires to respondents. The sample in this study used the convenience sampling method with the slovin formula, so 120 samples were obtained. The analysis method used is multiple linear analysis using SPSS version 20. The results of this study indicate that knowledge of tax regulations affects individual taxpayer compliance, taxpayer awareness affects individual taxpayer compliance, tax sanctions affect individual taxpayer compliance.